The effect of chilling on the properties of freshly slaughtered beef - ΔΙΔΥΜΟΠΟΥΛΟΣ ΓΕΩΡΓΙΟΣ (Journal of the Hellenic Veterinary Medical Society, 2019)
The lowering of temperature determines a slowing down of chemical, biochemical (e.g. enzymatic) and some physical processes. The chilling of freshly slaughtered meat does not, however, lead to a continuous reduction in the speed of those biochemical processes that take place after slaughter. The breakdown of adenosine triphosphate (ATP) and of glycogen slows down between body temperature (37 - 38°) and about +10°C, but when the temperature is lowered still further these reactions accelerate until a temperature of about -1°C is reached and this results in serious chortening of the muscle fibres (cold shortening), and thus also in increased toughness of the meat which cannot be removed by hanging. Cold shortening can only occur when rapid chilling brings the temperature in the meat down to below +10°C before most of the ATP has been broken down. We should therefore only expect meat to become tough in this way where freshly slaughtered meat is chilled rapidly and particularly in the case of small carcases such sa sheep and calwes. Barcases should therefore not be chilled to temperatures below + IOC until after the onset of rigor mort is. The cold shortening phenomenon is caused by calsium ions which can not be transported from the muscle fiblils into the sarcoplasmic reticulum if the temperature is too low and which therefore induce strong muscle contractions. The speed of post mortem biochemical changes increases at temperatures below + IOC, reaching a maximum at about 1 C and this occurs not only in meat in the piece but also in freshly slaughtered minced meat.